Social Services - Planning Commission, Government of India (Planning Commission, Government of India, 1951)
Health is a positive state of well being in which the harmonious development of physical and mental capacities of the individual lead to the enjoyment of a rich and full life. It is not a negative state of mere absence of disease. Health further implies complete adjustment of the individual to his total environment, physical and social. Health involves primarily the application of medical science for the benefit of the individual and of society. But many other factors, social, economic and educational have an intimate bearing on the health of the community. Health is thus a vital part of a concurrent and integrated programme of development of all aspects of community life.
Government of India Planning Commission
Government of India Planning Commission